Essential Oil Composition of Mentha longifolia (L.) Hudson from the Middle Region of Turkey - CELIK ONAR, HULYA; YASA, HASNIYE; YUSUFOGLU, AYSE; TANYOLAC, SULEYMAN (Asian Journal of Chemistry, 2010)
The essential oil of Mentha longifolia (L.) Hudson originating from the middle region of Turkey (Kirikkale) was obtained by steam distillation and clevenger-type method with a overall yield of 0.65 and 0.39 %, respectivelly. These essential oils were analyzed by capillary GC-MS using DB-5 and Carbowax-20M columns. Besides, the plant was examined by head-space method via PE-Wax. The essential oils are rich in linalool.